2022
DOI: 10.3390/app12010419
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Robots and Cobots Integration: A Preliminary Design of a Mechatronic Interface by Using MBSE Approach

Abstract: Enabling technologies that drive Industry 4.0 and smart factories are pushing in new equipment and system development also to prevent human workers from repetitive and non-ergonomic tasks inside manufacturing plants. One of these tasks is the order-picking which consists in collecting parts from the warehouse and distributing them among the workstations and vice-versa. That task can be completely performed by a Mobile Manipulator that is composed by an industrial manipulator assembled on a Mobile Robot. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In particular, the weight was compared with the payload, showing a very limited payload-to-weight ratio. Figure 1, taken from [10], shows the correlation between weight and payload among most of the currently available cobots. In this work, we focus on a multisensor direct interface for one-way communication from the human to the robot.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the weight was compared with the payload, showing a very limited payload-to-weight ratio. Figure 1, taken from [10], shows the correlation between weight and payload among most of the currently available cobots. In this work, we focus on a multisensor direct interface for one-way communication from the human to the robot.…”
Section: Related Workmentioning
confidence: 99%
“…The above-described robotic arms demonstrate relatively low payload-to-weight ratio performance, which restricts the physical assistance and payload that these cobots can support. In [ 10 ], the authors reported an extensive analysis of the available commercial cobots. In particular, the weight was compared with the payload, showing a very limited payload-to-weight ratio.…”
Section: Related Workmentioning
confidence: 99%
“…2.1. Industry 4.0 and the Increased Complexity of Systems Industry 4.0 refers to the fourth industrial revolution, which is characterized by the integrated adoption of advanced technologies such as the Internet of Things, artificial intelligence, and digital twins in production [19,20]. The interconnection of these technologies contributes to the creation of complex networks and data flows, which, in turn, require complex algorithms and software to manage and optimize their performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Robot installations are expected to grow over the next five years, based on a significant dominant sales trend (annual mean increase of 12% over 2017-2022), despite the global pandemic event and the contractions of some specific markets. COllaborative roBOTs (COBOTs) are classified based on reference frame location as fixed, mobile, and hybrid solutions [1][2][3]. The first class considers the robot placement in a time-invariant position, while the mobile configuration allows the robot motion.…”
Section: Introductionmentioning
confidence: 99%